Pengaruh Suhu Pengeringan pada Viabilitas Agen Hayati Pelet Bioferna Berbahan Dasar Limbah Ampas Tahu dan Pengaruhnya pada 2 Bibit Tanaman - fita fatma pratama; Sugiarto Sugiarto; Novi Arafita (AGRONISMA, 2022)
Biological fertilizer is a living microorganism material that is useful for increasing soil fertility and the quality of a plant's production. VP3 biofertilizer is a liquid biofertilizer formulation made from vermiwash as a carrier, molasses, PEG, and 3 functional bacterial isolates. In this study, the VP3 biofertilizer will be enriched with Trichoderma viride FRP3 in the form of pellets made from solid waste tofu dregs. The purpose of this study is to determine the appropriate drying temperature for the manufacture of BioferNA pellet fertilizer based on tofu waste and the drying results with the best total viability of biological agents will be tested on tomato and eggplant seeds to determine their effect on plant growth and the presence of symptoms of pathogenicity. and growth disorders. The research was carried out by the Microbiology Laboratory, Central Laboratory and Halal Center, Islamic University of Malang. The design used in the Biological Agent Viability Test was Completely Randomized (CRD) with 10 treatments and was repeated 3 times. While the design used in the test on plant seeds used a randomized block design (RAK) which consisted of 5 treatments and each was repeated 4 times. Observational data on each plant parameter were then tested using the analysis of variance F test with a significance level of 5%, if there was a significant effect between treatments followed by Duncan's test with a 5% level. The results showed that the drying temperature of BioferNA pellets made from tofu waste had a significant effect on the total viability of biological agents. The drying temperature of 40Â°C has a higher average total viability of biological agents than the temperature of 50Â°C. BioferNA pellets made from tofu waste which were added with VP3 and Trichoderma viride FRP3 had a significant effect on seedling height and fresh weight of eggplant and tomato seedlings, but had no significant effect on root length of tomato and eggplant seedlings.Keywords : Biofertilizer VP3, Trichoderma viride FRP3, Tofu waste, Tomato, Eggplant .